History Below the Waterline: Enslaved Salvage Divers Harvesting Seaports' Hinter-Seas in the Early Modern Atlantic. (26th March 2019) - Dawson, Kevin
Abstract: This article considers how enslaved salvage divers cooperated and conspired with slaveholders and white employers to salvage shipwrecks and often smuggle recovered goods into homeports, permitting them to exchange their expertise for semi-independent lives of privileged exploitation. Knowing harsh treatment could preclude diving, white salvagers cultivated reciprocal relationships with divers, promoting arduousness by avoiding coercive discipline while nurturing a sense of mutual obligation arising from collective responsibilities and material rewards. Enslaved salvagers were, in several important ways, treated like free, wage-earning men. They were well fed, receiving daily allowances of fresh meat. Most resided in seaports, were hired out, and received equal shares of recovered goods, allowing many to purchase their freedom and that of family members. Divers produced spectacular amounts of wealth for their mother countries, owners, and colonial governments, especially in the maritime colonies of Bermuda, the Bahamas, and Cayman Islands. Their expertise was not confined to maritime colonies. Even as plantation slavery was taking root during the mid-seventeenth century, salvage divers provided an important source of income for planter-merchants.